Bangladesh Rural Advancement Committee auditors' report and financial statements for the year ended December 31, 1996 - BRAC (© BRAC, 2016)
This Financial Statement prepared by Acnabin & Co. Chartered Accountants, National Scout Bhaban (13th floor), 70/1 Inner Circular Road, Kakrail, Dhaka- 1000, Bangladesh